The variation in the number of roots and canals morphology of permanent mandibular first molar teeth by using cone beam computed tomography imaging in a sample of Erbil city - Hassan Ali Mahmoyd Albarzanji; Alaa Muhamed Sadiq Muhamed Jamil (Erbil Dental Journal)
Background and Objectives: Adequate knowledge about the number of roots, canals, and morphology of lower first molar teeth is a basic requirement of root canal therapy and any surgical treatment in this region, was carried out to investigate root and canal morphology of permanent mandibular first molars in a sample from Erbil population using cone beam computed tomography (CBCT).